The Effectiveness of Warm Water Foot Sound with Salt and Lavender Flower Extract on Sleep Quality in Elderly with Insomnia - Fajar Surahmi (Green Publisher Indonesia, 2022)
Insomnia is a sleep disorder at night. Soaking feet in warm water with a mixture of salt is a nursing action and non-pharmacological method that can help a person to be more relaxed and comfortable. Lavender (Lavandula angustifolia) has a sedative effect because it has the main active ingredient, linalool (C10H18O). The mechanism of lavender flower aromatherapy (Lavandula angustifolia) which contains linalool by stimulating an area in the brain, namely the nucleus raphe which will secrete serotonin which can send a person to sleep. The design of this research is a pre-experiment with a one group pre test and post test design. The sample of this study were 34 elderly respondents who were in Rampelsos Pucang Gading Semarang. The results of the study: Most of the characteristics of the elderly (70.6%) were aged 60 – 74 years. Of the 34 respondents, dominated by male respondents, 23 were male respondents. The educational background of the elderly respondents who became the object of most research was Junior High School, which was 35.3%. Prior to treatment, 100% of respondents had poor sleep quality. After treatment, 91.2% of respondents had poor sleep quality and 8.8% experienced good sleep quality. The results of the analysis using statistical tests showed that p = 0.000 means that there is an effect of soaking the feet in warm water with a salt solution and a mixture of lavender flower extract on sleep quality of elderly respondents.